The Landscape Design of the Art Nouveau Style - Makhmudova, Malika; Jumaniyazova, Dilfuza; Abdullahodjaev, Gayrat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article describes some of the features of the development of landscape design in the Art Nouveau style and its application in the modern world. In particular, it presents the main features of the style, its appearance and the main masters, such as Antonio Gaudi. The Art Nouveau style has been widely used in modern life, as well as landscape design, which is expressed through a particular interpretation of the basic rules and compositional techniques, colour solution of small garden, plant selection and combinations thereof, types of decorative paving, small architectural forms and garden equipment.